Moral Cartography: Classifications of Village Residents in the Everyday Life of Rural Bureaucrats (Антропологический форум / Forum for Anthropology and Culture, 2024)
The article analyses the classifications of the residents of settlements used by rural bureaucrats (employees of rural administrations and members of their teams). The analysis is based on materials gathered through participant observation in two rural settlements in southwestern Siberia. The principles by which the “characters” of villages are distinguished are examined, i.e. in what contexts a “moral cartography” of localities takes place. The study shows that the most frequent differentiating features in the bureaucratic characterisation of villages are: 1) the independence of residents in solving their problems or addressing the requirements of the administration; 2) the community’s cohesion and willingness to help bureaucrats in governance or lack thereof. These classification signs relate to the “problematic nature” of the village for rural bureaucrats, i.e. the possibility of conflicts, complaints and claims. The author concludes that one of the functions of the bureaucratic classification of villages is contingency coping strategy, which is characteristic of the task-oriented work of rural bureaucrats. Knowledge of the “character” of the inhabitants of settlements allows officials to form expectations, develop work strategies and explain managerial successes and failures. In addition, the ability to map the social space of a village is important for confirming the status of rural governors and especially the heads of rural administrations. Faced daily with a shortage of administrative and material resources, rural bureaucrats find their own intermediate positions to be vulnerable. However, the “proper” knowledge of social space allows them seemingly to reverse their dependent position. In accordance with the principle of the administrator’s responsibility for a given space, the classifications of villages afford local officials the opportunity to demonstrate a comprehensive knowledge of the territory, thereby testifying to their status as “owners” (khozyaeva) of the land.